2023
DOI: 10.1002/hyp.15025
|View full text |Cite
|
Sign up to set email alerts
|

Headwater stream temperature response to forest harvesting: Do lower flows cause greater warming?

R. Dan Moore,
S. M. Guenther,
Takashi Gomi
et al.

Abstract: This study addressed two hypotheses regarding the relationship between stream temperature response to shade removal and streamflow: (a) that temperature response increases as flow declines and (b) that the relationship can be complicated by shifts in dominant streamflow sources and pathways during low‐flow periods. The study was based on a paired‐catchment design in rain‐dominated headwater catchments in the southern Coast Mountains of British Columbia, Canada, and focused on the effect of a 50% thinning treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Moore, Sutherland, et al (2005) introduced the use of time series regression to address issues with temporal autocorrelation of the residuals when using sub‐annual time series. An advantage of using sub‐annual time series is that it allows analysis of the temporal variability of stream temperature response to forest cover changes in relation to seasonal and weather‐related effects (Gomi et al, 2006; Moore et al, 2023; Oanh et al, 2021), which may be important when considering the potential for impacts on different life‐history stages for a species of concern.…”
Section: Overview Of Empirical Study Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moore, Sutherland, et al (2005) introduced the use of time series regression to address issues with temporal autocorrelation of the residuals when using sub‐annual time series. An advantage of using sub‐annual time series is that it allows analysis of the temporal variability of stream temperature response to forest cover changes in relation to seasonal and weather‐related effects (Gomi et al, 2006; Moore et al, 2023; Oanh et al, 2021), which may be important when considering the potential for impacts on different life‐history stages for a species of concern.…”
Section: Overview Of Empirical Study Designsmentioning
confidence: 99%
“…Decades of research in a range of forest ecosystems have demonstrated that reductions in riparian shade by logging, vegetation management or natural disturbance result in summertime warming by increasing the amount of solar radiation reaching the stream (Bladon et al, 2018;Brown, 1969;Isaak et al, 2010;Leach et al, 2022;Leach & Moore, 2010;Lynch et al, 1984;Raulerson et al, 2020;Rex et al, 2012;Rishel et al, 1982;Rowe & Pearce, 1994;Rowe & Taylor, 1994;Stott & Marks, 2000). The magnitude of post-harvest warming depends not only on the amount of shade reduction, but also factors such as catchment area, channel morphology and substrate, weather conditions, and the quantity and source components of stream discharge (Beyene & Leibowitz, 2024;Coats & Jackson, 2020;Gomi et al, 2006;Janisch et al, 2012;Miralha et al, 2024;Moore et al, 2023;Oanh et al, 2021). Post-harvest stream warming has historically been of concern in relation to the potential degradation of thermally suitable habitat for cool and coldwater aquatic species such as salmonids (e.g., Cunningham et al, 2023) and some amphibians (e.g., Jackson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%